Impacts of Population Density for Landuse Assessment in Cengkareng, West Jakarta, Indonesia: Landuse Assessment - Ratih Fitria Putri; Aji Wijaya Abadi; Naufal Fattah Tastian (UIR PRESS, 2020)
Economic development in Jakarta has been influencing physical and social characteristics of urban area significantly. For recent years, burgeoning population growth occurs as a result of urban development and contributes to the landuse dynamics in a certain area. Cengkareng, is one of the most developed urban areas in Jakarta and has been experiencing such population and landuse dynamics. Its strategic location has turned this area becomen densely-populated. Increasing population density increase land demand, shapes the settlement pattern, and changes the landuse of the area. A study conducted in Cengkareng District has been done to describe how the population density impacts the landuse features for landuse assessment. The method implemented in this study combines quantitative and qualitative to process statistics and satellite imagery to produce data of population density, landuse change, and settlement pattern of the studied area. The study resulted that Cengkareng has experienced such significant landuse change which is dominantly converted into settlement and offices due to rising of population density. Nucleated settlement pattern has taken more area regarding to increased land need over land supply. It becomes serious problem for Cengkareng such aa slum settlements, flood problems, and land subsidence. Keywords: Landuse change; Population density; Settlement pattern